Lung cancer screening: advancing early detection and improving outcomes - Geertruida H. de Bock (Holistic Integrative Oncology)
Abstract Lung cancer remains the leading cause of cancer death worldwide, mainly due to late diagnoses. While low-dose computed tomography (LDCT) screening reduces mortality in high-risk groups, false positives and low nodule specificity remain major challenges. High nodule prevalence even in nonsmokers further highlights the need for better risk stratification. Improved screening may be achieved through refined nodule assessment, sex-specific models, and emerging biomarkers like blood-based assays. Integrating these tools can enhance accuracy and reduce harms. Continued efforts to promote smoking cessation and improve air quality are also crucial.